História, memória, fronteira e alteridade em Lavrinhas de São Sebastião nas “Cartas de Goiás” de Carlos Pereira de Magalhães (1919-1925) - Ferreira, Gleisson (2018)
The present work has as object of study the memory of and on the quilombola communities of Lavrinhas de São Sebastião from the contents of the book "Charts of Goiás in the beginning of the XXth century", by Carlos Pereira de Magalhães, and based on the concepts of history, memory, frontier and otherness, addressing the worldviews that establish the differences, especially cultural, between individuals and societies. We thus seek to discuss elements of alterity that can be verified in the author's views, which the work in question denotes, in relation to the society of Goiás in general, and specifically to that of Lavrinhas de São Sebastião. It is a region that houses communities remaining in the gold and quilombos cycle. This statement is reinforced by testimonies collected locally by the author in the early twentieth century, and by the interviews we conducted for the development of this dissertation, so the analysis of the concept of memory becomes here, essential. In the lands of this former Sesmaria de Lavrinhas de São Sebastião, several quilombola communities emerged, however, in this work we only approached the community of the village of Lavrinhas and the community of Porto Leocárdio, far from Lavrinhas three kilometers approximately. We make an analysis from the decolonial perspective we seek a historicity that corroborates this quilombola ancestrality. We sought to trace a history of the region from the beginning of the exploration of the gold mines, with the numerous slaves, the escapes of slaves and formation of quilombos, the expropriation of lands by economic groups and the forms of resistance of the community.